Spontaneous Fluctuations between Diagnostic and Nondiagnostic ECGs in Brugada Syndrome Screening: Portuguese Family with Brugada Syndrome - Santos, Luis Ferreira dos (2017)
BACKGROUND: All family members of patients with Brugada syndrome (BS) should be screened. Fluctuations between diagnostic and nondiagnostic electrocardiogram (ECG) patterns in patients with BS are recognized, but systematic studies are lacking. The objective of this work was to prospectively evaluate the spontaneous changes between diagnostic and nondiagnostic ECG patterns in a family screened for BS. METHODS: One hundred twenty-nine family members were possibly affected plus the index case were screened with two ECGs with an interval of 6 months. Only coved-type ECG pattern was defined as diagnostic; type 2 and 3 ECGs were considered suggestive. RESULTS: The first ECG series made six diagnostics and the second 11, but only three patients maintained the diagnostic ECG. Patients with basal diagnostic ECG were older and more frequently symptomatic. Body mass index (BMI) was significantly lower in adults with diagnostic plus suggestive ECG when compared with the others. No significant gender difference was found among relatives with or without diagnostic ECG. CONCLUSION: Spontaneous phenotypic manifestation of BS was more frequent in older symptomatic patients, absent in children, and related with low BMI. ECG manifestations were intermittent in more than 3/4 of the affected patients. Fluctuations between diagnostic and nondiagnostic ECGs may have an implication on the correct phenotyping in family screening so several ECGs with drug challenging are mandatory.